MyDocShelves: integrated mobile platform for digital content management - Abdul Jamil@Kamarudzzaman, Azura; Mohammad, Al-Bakri; Mohd Zaki, Faddliza; Md Yatim, Norhidayu; Nasharudin, Nurhidayah; Jamin, Jashira (Universiti Teknologi MARA, Kedah, 2017)
MyDocSHELVES is a software platform that incorporates technology, tools, and methods which functions to manage, store, preserve, deliver and access the electronic document in single integrated storage. MyDocSHELVES help create, categorize, index, search, retrieve and share various forms of digital contents in audio/video/text formats. Thus, the process of accessing the information become easier, faster, interesting, effective and efficient. This platform is developed for the purpose of online access as well as mobile application using Q-R code technology. MyDocSHELVES focuses on digital content management such as mobile teaching and learning, electronic content materials in information agency such as library, archives and resources center, corporate memory management and digital archives for documents and photos. This innovation will solve the problem of organization in place of their electronic publication effectively. An alternative to the printed publication which requires high cost; minimizing in cost of printing. Information can be reached by the users quickly and efficiently around the clock availability. All information stored in one integrated platform.